Sociodemographics and access to organic and local food: A case study of New Orleans, Louisiana. (September 2018) - Li, Chuo; Ghiasi, Amir; Li, Xiaopeng; Chi, Guangqing
Abstract: This study examined the association between physical accessibility to organic and local food, and sociodemographic factors in New Orleans, Louisiana. Spatial regression models were used to investigate how sociodemographic variables such as income, race/ethnicity, education, and age correlate with driving, bicycling, and walking distances to stores that sell organic or local food. The distances were calculated from GIS and real-time speed information from Google Maps. The results indicated that physical access to such stores is positively associated with population density, median housing value, education, non-Hispanic Blacks, and Hispanics, and is negatively associated with median housing age. We found no disparities in access to organic and local food on the basis of income and race. Highlights: Density, housing value, education affect access to organic and local food positively. Access to organic and local food is negatively associated with median housing age. No disparities in access to organic and local food on the basis of income and race Spatial regression outperforms standard linear regression in accessibility analysis.